THE IMPORTANCE OF PROFILING IN IDENTIFYING NARCOTIC DRUGS - MUSAEV, Djamaliddin (Journal of Fundamental Studies, 2025)
The article characterizes profiling as a method of personality psychodiagnostics used to identify individuals who use the peculiarities of the intracavitary method of transporting drugs, and reveals some tactical techniques and features of profiling to identify drug couriers in passenger traffic. Existing and actively used means of protection are focused mainly on the detection of narcotic drugs using, for example, technical means, sniffer dogs and security measures. However, these technologies do not allow identifying illegal intentions. Many years of successful experience in using the profiling method abroad, the positive results obtained also confirm the practical usefulness of this method in training law enforcement officers.